A screening study on extractive content and composition of Scots pine heartwood of three stands with close proximity and their resistance against basidiomycetes. (2nd January 2017) - Zimmer, K.; Melcher, E.
Abstract : The extractive content of inner and outer heartwood of nine Scots pine trees from three different stands in Norway was determined by automated solvent extraction and biological screening tests were performed using basidiomycetes. The evaluation of mass spectra by means of a NIST library search shows that in the petroleum ether extracts α-pinene and carene as well as terpinene and cadinene derivatives are the main extractives found in both inner and outer heartwood. In the inner heartwood, however, these substance groups were found in lower quantities. These substances mainly have a hydrophobic effect. The screening tests indicate that also extractive-rich heartwood is extremely degraded by Poria placenta which corresponds to the analytical results of the petroleum ether extracts.